Factors Affecting EFL University Students' Listening Comprehension - Usya'bani, Asyfi Hidayat; Purwaningsih, Sundari; Solihati, Tri Agustini (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2025)
Mastering listening comprehension remains a significant challenge for EFL university students. This study aimed to identify the factors affecting the mastery of listening comprehension among these students. A survey design was employed, involving English Education Department students from the classes of 2020–2023. The data collection methods used were closed-ended questionnaires, open-ended questionnaires, and semi-structured interviews. The findings revealed several factors affecting students' listening comprehension, categorized into four main areas: listening content, speakers, physical setting, and listeners. Listening content emerged as the most influential factor, with unfamiliar vocabulary, audio quality, and speech rate presenting significant challenges. Other notable factors included pronunciation and accent variations, environmental distractions, and students' motivation and proficiency levels. They suggest that teachers and students should collaboratively identify learning strategies tailored to address specific challenges in listening comprehension. Furthermore, the study underscores the importance of carefully selecting listening materials that align with students' proficiency levels, particularly in terms of vocabulary. Finally, the findings indicate a need for strategies to enhance student motivation and encourage regular listening practice. This research contributes to our understanding of the complexities involved in EFL listening comprehension and provides valuable insights for improving teaching and learning strategies in this critical language skill.